Fusion of locomotor maneuvers, and improving sensory capabilities, give rise to the flexible homing strikes of juvenile zebrafish - Westphal, Rebecca E.; OMalley, Donald M. (Frontiers in Neural Circuits, 2013)
At five days post-fertilization and 4 mm in length, zebrafish larvae are successful predators of mobile prey items. The tracking and capturing of 200 µm long Paramecia requires efficient sensorimotor transformations and precise neural controls that activate axial musculature for orientation and propulsion, while coordinating jaw muscle activity to engulf them. Using high-speed imaging, we report striking changes across ontogeny in the kinematics, structure and efficacy of zebrafish feeding episodes. Most notably, the discrete tracking maneuvers used by larval fish (turns, forward swims) become fused with prey capture swims to form the continuous, fluid homing strikes of juvenile and adult zebrafish. Across this same developmental time frame, the duration of feeding episodes become much shorter, with strikes occurring at broader angles and from much greater distances than seen with larval zebrafish. Moreover, juveniles use a surprisingly diverse array of motor patterns that constitute a flexible predatory strategy. This enhances the ability of zebrafish to capture more mobile prey items such as Artemia. Visually-guided tracking is complemented by the mechanosensory lateral line system. Neomycin ablation of lateral line hair cells reduced the accuracy of strikes and overall feeding rates, especially when neomycin-treated larvae and juveniles were placed in the dark. Darkness by itself reduced the distance from which strikes were launched, as visualized by infrared imaging. Rapid growth and changing morphology, including ossification of skeletal elements and differentiation of control musculature, present challenges for sustaining and enhancing predatory capabilities. The concurrent expansion of the cerebellum and subpallium (an ancestral basal ganglia) may contribute to the emergence of juvenile homing strikes, whose ontogeny possibly mirrors a phylogenetic expansion of motor capabilities.